Length-weight relationship, breeding season, sex ratio, maturity and fecundity of the Nile catfish Synodontis schall (Bloch and Schneider, 1801) (Pisces: Mochokidae) in Lake Chamo, Ethiopia - Dadebo, Elias (Ethiopian Journal of Science and Technology, 2025)
Length-weight relationship and some aspects of reproductive biology of the Nile catfish Synodontis schall (Bloch and Schneider, 1801) in Lake Chamo, Ethiopia were studied from fish sampled in each month during January to December 2010. The relationship between fork length (FL) and total weight of males (TW = 0.020FL3.207, R2 = 0.965, n = 277), females (TW = 0.020FL3.248, R2 = 0.976, n = 407) and the sexes combined (TW = 0.020FL3.240, R2 = 971, n = 684) were curvilinear and statistically significant (ANOVA, P<0.05). The proportion of breeding fish was high between May and September, during which time 46.8% - 72.0% of the males and 41.3% - 77.9% of the females had ripe gonads. Thus, the months with high proportions of breeding fish were considered as the breeding season of the fish. More number of females was caught in all size classes but sex ratios were significantly different from 1:1 in size classes 30.0- 34.9 cm FL and 35.0- 39.9 cm FL. The overall male to female sex ratio of 1:1.39 was also significantly different (Ï‡2 = 24.71, P<0.001) from the theoretical ratio of 1:1. Size at first maturity of males was 23.1 cm FL while that of females was 26.4 cm FL. Fecundity ranged from 3,500- 54,089 eggs with a mean of 21,017 eggs. The mean relative fecundity of S. schall was 76.1 eggs g-1 of body weight. The average number of eggs g-1 of ovary (preserved wet weight) ranged from 983 to 3,797 with a mean of 1,847 eggs g-1. The relationships between fecundity and fork length and fecundity and total weight were curvilinear while the relationship between fecundity and ovary weight was linear.